2020
DOI: 10.1136/vetreco-2020-000399
|View full text |Cite
|
Sign up to set email alerts
|

A survey of biosecurity measures and serological status for bovine viral diarrhoea virus and bovine herpesvirus 1 on dairy cattle farms in north‐west and north‐east Spain

Abstract: BackgroundBiosecurity is a key measure to reduce and prevent the introduction of diseases to farms and minimise spread of diseases within a herd. The aim of the study was to characterise the current application of biosecurity measures on dairy cattle farms in Spain along with their bovine viral diarrhoea and infectious bovine rhinotracheitis status.MethodsData on biosecurity measures for 124 dairy herds were collected using a questionnaire. The sanitary status of these farms for bovine viral diarrhoea and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Although purchased cattle are considered to be the main risk factor for disease entry to dairy farms [ 11 , 12 , 18 , 25 ], the importance of other measures should not be underestimated and may result in less use of monetary and labor resources intended for control programs. Other practices to which veterinarians give high scores (>7 out of 9) are less frequently observed in the study population [ 19 ]. Although it has been suggested that interspecies transmission of some MAP strains may not be a rare event if there is close contact between different species at the farm level [ 29 ], a small proportion of farms kept small ruminants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although purchased cattle are considered to be the main risk factor for disease entry to dairy farms [ 11 , 12 , 18 , 25 ], the importance of other measures should not be underestimated and may result in less use of monetary and labor resources intended for control programs. Other practices to which veterinarians give high scores (>7 out of 9) are less frequently observed in the study population [ 19 ]. Although it has been suggested that interspecies transmission of some MAP strains may not be a rare event if there is close contact between different species at the farm level [ 29 ], a small proportion of farms kept small ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that interspecies transmission of some MAP strains may not be a rare event if there is close contact between different species at the farm level [ 29 ], a small proportion of farms kept small ruminants. Furthermore, animal movement to cattle fairs or competitions (with return of the animals) is a possible disease transmission pathway for few farms in the region, and farms that allow calves to graze are also scarce [ 19 ]. In any case, within a herd, it is the younger animals that are the most susceptible to contracting MAP, and this tends to move slowly through soils and remain on the grass and in the upper layers of pasture soil, posing an infection hazard for grazing animals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this country, very poor information is available regarding IBR control plans. According to Villaamil et al (2020), in Galicia (north-west of the country), an official voluntary IBR control plan has been in place since 2004 and now involves a large proportion of the cattle population. The program is based on a serological survey of herds and progressive seroprevalence reduction, by means of replacement control and not by culling animals.…”
Section: Spainmentioning
confidence: 99%